Correlation of skull vibration-induced nystagmus test and video head impulse test in patients with sudden sensorineural hearing loss with vertigo - Guo, Qiang; Lin, Ying; Hang, Pengfei; Zha, Dingjun (Frontiers in Neurology, 2025)
ObjectiveThe study aims to examine the agreement between the skull vibration-induced nystagmus test (SVINT), video head impulse test (vHIT), and caloric test (CaT) in detecting vestibular function asymmetry in patients with unilateral sudden sensorineural hearing loss with vertigo (SSNHL-V).MethodsThis study included 71 patients with SSNHL-V and 20 healthy controls. All participants underwent comprehensive audiological and vestibular function assessments. This study evaluated the correlation between SVINT and CaT/vHIT in detecting vestibular asymmetry. Furthermore, we analyzed the correlation between SVINT findings and (1) the classification of audiograms, and (2) the degree of hearing loss in SSNHL patients with vertigo.ResultsThe agreement between the result of SVINT and horizontal semicircular canal (HSCC) results of vHIT (kappa = 0.668, p < 0.05) was superior to that between the SVINT and CaT (kappa = 0.324, p < 0.05), as well as between the SVINT and vertical semicircular canal (SCC) results of vHIT (kappa = 0.345, p < 0.05). SVINT had a sensitivity of 96.7% and a specificity of 73.2% when using the HSCC results of vHIT as the standard. The SVINT did not correlate with the classification of the audiogram and the degree of hearing loss (F = 5.968, p > 0.05; χ2 = 0.017, p > 0.05).ConclusionSkull vibration-induced nystagmus test is a bedside test that enables simple and rapid screening for a high-frequency functional asymmetry of HSCC in patients with sudden sensorineural hearing loss with vertigo.